Peningkatan Literasi Digital Guru SDN 1 Jalupang Tigaraksa Melalui Pelatihan Media Pembelajaran Berbasis ICT - Darmansyah, Ady; Amaliah Sholihah, Siti; Saadah (Universitas Tangerang Raya, 2022)
Digital literacy is crucial in facing the current digital era, especially for elementary school teachers. This research aims to enhance the digital literacy of teachers at SDN 1 Jalupang Tigaraksaa through training on Information and Communication Technology (ICT)-based learning media. The activity's partner is SDN 1 Jalupang Tigaraksa with a total of 10 teacher participants. The implementation method involves conducting intensive training covering basic ICT concepts, strategies for developing ICT-based learning media, and practical implementation within the context of elementary school education. The training is tailored to the needs and level of digital technology understanding of the teachers. The results of this training show a significant improvement in the digital literacy of teachers at SDN 1 Jalupang Tigaraksaa. They are better able to understand basic ICT concepts and effectively integrate them into classroom learning. Additionally, participants are capable of developing various ICT-based learning media that align with curriculum requirements and student characteristics. Consequently, this ICT-based learning media training successfully enhances the digital literacy of teachers at SDN 1 Jalupang Tigaraksaa. It is hoped that this training will have a positive impact on improving the quality of education and student achievement in the future.